A Critical Assessment of 'Forgiveness' in Post-atrocity Reconciliation - Magnus,Edwina Sophia (2025)
This thesis critically engages with the concept of forgiveness in the context of reconciliation between Aboriginal and Torres Strait Islander Peoples and non-Indigenous Australians. It examines first the historical development of reconciliation efforts between Indigenous and white Australia and shows a discrepancy between their approaches. Where First Nations Australians emphasise concrete structural changes and legal reform, white Australia takes a ‘softer’ approach, centered on forgiveness and recognition. Secondly, the thesis analyses political forgiveness as used in the Australian context. This is conducted using an interdisciplinary approach, drawing on critical legal and political theory. Engaging with legal and philosophical sources, three criteria are extracted which are essential for forgiveness. These three criteria; the perspective criteria, the temporal criteria and the non-obligatory criteria are analysed in turn. It is shown that Australia fails to meet these criteria, both due to its status as a settler-colonial state and its concrete laws and policies which violate Indigenous Australians individual and collective rights. The purpose of this exercise is to engage directly with forgiveness as a method of reconciliation and assess its viability as a tool for reconciliation, rather than critique it with reference to other methods being more effective. Forgiveness is here also contextualized as a foundational principle in law and placed in the broader peace v justice debate of post-conflict discourse. The thesis concludes that forgiveness in Australia is perpetuated despite its unviability as it maintains settler legal hegemony and undermines calls for justice and reparations, legal structural reform and First Nations sovereignty and right to self-determination.
Keywords: Jurisprudence; Post-conflict Reconciliation Mechanisms; Rights of Indigenous Peoples; Aboriginal and Torres Strait Islander Peoples